Brain atlas for functional imaging clinical and research applications - Nowinski, Wieslaw L.; Thirunavuukarasuu, A.; Kennedy, David N. (Stuttgart : George Tieme Verlag, 2001)
'This CD-ROM provides numerous tools for the triplanar analysis of functional images. It contains the fully color-coded and labeled Talairach-Tournoux brain atlas in the axial, coronal, and sagittal orientations, along with Brodmann's areas and gyri in the axial orientation.'--Container
CD's are available at Koleksi Media Perpustakaan HUKM
System requirements for Windows: PC with 486 processor or better (Pentium recommended); 8 MB RAM; Windows 95/98/2000/NT; CD-Reader 12x minimum; 65,000 color minimum (16 bits)
System requirements for Macintosh: 68030 processor or better or Power PC; 8 MB RAM; System 7.0 or higher; CD-Reader 12x minimum; 65,000 color minimum (16 bits )
Keywords: Brain -- imaging -- atlases -- software; Brain -- anatomy -- atlases -- software; Three-dimensional imaging in medicine -- atlases -- software